PENYUSUNAN LAPORAN ARUS KAS PADA PRIMKOP KARTIKA S-11 BHALADIKA SEMARANG TAHUN 2020 - Adibatul Isna; Didiek Susilo Tamtomo; Sulistiyo Sulistiyo (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2021)
This study aims is to prepare the statement of cash flow and analyze thecash flow statement in 2020 at Primkop Kartika S-11 Bhaladika. Data collection was obtained by interview and documentation, while methods of writing used aredescription and exposition. Description method to describe comparative balancesheets as of December 31, 2020 and 2019, calculation of business results for the year ended December 31, 2020, and selected data transaction Primkop Kartika S-11 Bhaladika for 2020. Exposition method to clarify about changes in cash and cash equivalents, cash flows from operating activities, investing activities, and financing activities. The result of this study is the cash flow statement of Primkop Kartika S-11 Bhaladika in 2020 can be prepared and presented. The statement of cash flow shows positive cash flow in operating activities of Rp 629.577,163.00, and positive cash flow in investing activities of Rp 976,769,854.00, and positive cash flow in financing activities of Rp 285,951,078.00. Analysis of cash flow statement indicates idle cash at Primkop Kartika S-11 Bhaladika Semarang in 2020.